The Influence of Professionalism, Capabilities and Work Culture on the Performance of Regional Secretariat Employees of South Sulawesi Province - Muh Said; Andi Djalanete; Basri Rahman (PINISI Discretion Review, 2022)
study aims to determine and analyze the effect of professionalism, capability and work culture on the performance of the regional secretariat employees of South Sulawesi Province. The research approach used in this study is a quantitative method. The population is all employees of the Regional Secretariat of South Sulawesi Province, totaling 90 people. From these data, the unit of analysis is taken from the number of civil servants (PNS) so that the census method is a method that is in accordance with the conditions that exist in the Regional Secretariat of South Sulawesi Province, totaling 90 respondents. The results show that professionalism has a positive and significant effect on employee performance at the Regional Secretariat of South Sulawesi Province, as well as capability has a positive and significant impact on employee performance at the Regional Secretariat of South Sulawesi Province. Work culture has a positive and significant influence on employee performance at the Regional Secretariat of South Sulawesi Province. The value of the coefficient of determination (R square) is 53.3 % which means that all independent/independent variables (X) have a contribution to performance while the rest are not included in the study.